2003
DOI: 10.1096/fj.02-0918fje
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous generation of methane, carbon dioxide, and carbon monoxide from choline and ascorbic acid ‐ a defensive mechanism against reductive stress?

Abstract: Indirect evidence suggests that an abnormal increase in reducing power (reductive stress) may be associated with abnormal clinical states. We have recently proposed that under such conditions biomolecules with electrophilic methyl groups (EMGs) bound to positively charged nitrogen or sulfur moieties may act as electron acceptors and that this poising mechanism may entail the generation of methane gas. Here we report for the first time the generation of methane by rat liver mitochondria. We also report the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 32 publications
4
49
0
Order By: Relevance
“…This is in accordance with the findings of Ghyczy et al 9,12 who demonstrated that endothelial cells from rat liver produced CH 4 when exposed to site-specific inhibitors of the ETC. It would seem that aerobic CH 4 formation is not only a result of chemical formation from dead biomass as previously shown by several studies 8,11 but might also have a physiological role in eukaryotic groups such as fungi, animals and plants.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in accordance with the findings of Ghyczy et al 9,12 who demonstrated that endothelial cells from rat liver produced CH 4 when exposed to site-specific inhibitors of the ETC. It would seem that aerobic CH 4 formation is not only a result of chemical formation from dead biomass as previously shown by several studies 8,11 but might also have a physiological role in eukaryotic groups such as fungi, animals and plants.…”
Section: Discussionsupporting
confidence: 93%
“…Less well known are the findings of Ghyczy et al 9,12 who demonstrated that endothelial cells from rat liver produced CH 4 when exposed to site-specific inhibitors of the electron transport chain (ETC). A similar observation has been made for plant cell cultures grown under sterile and oxic conditions 13 .…”
mentioning
confidence: 99%
“…In vivo and in vitro studies have provided persuasive evidence of animal CH 4 production under stress conditions (Ghyczy et al, 2003(Ghyczy et al, , 2008aTuboly et al, 2013a;Tuboly et al, 2013b). Sodium azide (NaN 3 ) administration is a widely used method to cause mitochondrial dysfunction (Ghyczy et Fungous Methionine a Postulated reaction schemes for CH 4 production in plants and fungi (reaction ①) as well as animals (reaction ②).…”
Section: Animalsmentioning
confidence: 99%
“…Moreover, NaN 3 treatment causes reactive oxygen species (ROS) production (Ji et al, 2011;Tuboly et al, 2013b). Hypoxic mitochondrial CH 4 production was found in rats (Ghyczy et al, 2003;Tuboly et al, 2013b), and such CH 4 -generating capacity has proved to be independent of the methanogenic flora because it persists after antibiotic treatment targeting the gastrointestinal methanogenic archaea. CH 4 production can occur not only in rat mitochondria but also in bovine endothelial cells under hypoxic conditions (Ghyczy et al, 2008a).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation